The labor reform implemented during the second government of Alfonso López Pumarejo - Toscano, Óliver Mora (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article studies the most relevant elements of the labor reform proposedand implemented by President Alfonso López Pumarejo during hissecond term of government. The reform was implemented fundamentallyacross the Law 6th of 1945. The most relevant elements of this reformwere the institutionalization and regulation of the labor movements thatcontribute in this way to the stability of the economic growth and the businessdevelopment claimed in this moment for the Colombian State, aswell as the recognition of a set of claims and rights to urban workers, thatmade of this reform the most advanced in Colombia in social terms duringthe 20th century.